Developmental coordination disorders and its treatment in school children: An overview - L. M. Ruiz; E. Mata; J. A. Moreno (Asociación Española de Ciencias del Deporte, 2010)
It is necesary to accept the presence of children with motor coordination problems in our schools. Research in the last decade has demostrated this situation and together with the clasical expresion of clumsy, the interest of educators, physicians and psychologists for this syndrome have increased, and new expresions and considerations have emerged. The development of intervention programs with the objective of remediating this problem has manifested different approaches, rationales and theories that support them. Some of them maintain the necessity of developing the processes that underlying children's motor behavior and the other promote to develop the specific motor skills that permit them to interact and to be competent with others, and objetcs, in the playground and the gymnasium. This review analyzes the role of these approaches and their empirical support, and emphasizes the role that physical education can have in this process of developing motor competence in the school. Key words: Motor Competence, developmental coordination problems, clumsiness, physical education, intervention, schoolchildren